Simulating experiment on the hydrothermal superimposing metallogenesis of the Dongguashan strata-bound copper deposit - 徐兆文 华明 陆现彩 杨小男 饶冰 王云建 蒋少涌 陆建军 聂桂平 黄顺生 (Acta geochimica, 2007)
Series of sedimentary hydrothermal-diplogenetic copper deposits have been found scattering in the region along the middle-lower reaches of the Yangtze River, and their metallogenetic mechanism is still in hot debate. In order to reveal the ore-forming kinetics of sedimentary process and hydrothermal superimposition, and evaluate the role of sedimentary pyrite in the enrichment and precipitation of copper, a set of simulating experiments on the reaction between pyrite and CuC12 solution were conducted. According to the physicochemical characteristics of the ore-forming fluid of the Dongguashan copper deposit, Anhui Province, 100 MPa was selected as the experimental pressure, and the experimental temperatures were set at 450, 350, 250 and 150~C, respectively. The reactions between pyrite grains isolated from the Shimenkou strata-bound pyrite deposit and the solution with 0.2 mol/L CuC12 and 1.0 mol/L NaC1 were experimentally simulated. Then, variations in surface topography and surface chemistry of the experimental pyrite grains were documented using scanning electronic microscopy （SEM）, atomic force microscopy （AFM）, Auger electron spectrometry （AES） and X-ray photoelectron spectroscopy （XPS）, and the solution and newly formed minerals were analyzed using inductively coupled plasma （ICP-AES） and X-ray diffraction （XRD） techniques. Desulphurization of pyrite surface was observed and new copper minerals were detected. It is proposed that pyrite can act as a geochemical barrier for the enrichment and precipitation of copper from the solution under the experimental conditions. Furthermore, the ore-forming mechanism of sedimentary hydrothermal-diplogenetic copper deposits was discussed.